2007
DOI: 10.1186/1749-8090-2-21
|View full text |Cite
|
Sign up to set email alerts
|

Superior epigastric artery pseudoaneurysm- a rare complication of chest drain insertion in coronary artery bypass grafting

Abstract: BackgroundAlthough chest drain insertion during coronary artery bypass grafting is a fairly standard procedure, however it may result in extremely rare complications.Case presentationThis is the first case being reported that demonstrates a pseudoaneurysm of superior epigastric artery resulting from chest drain insertion following coronary artery bypass grafting.ConclusionAdequate caution should be used along with good understanding of the anatomical landmarks during apparently simple and standard operative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Review of abstracts (Fig. 1) led to 155 papers selected for further review, and subsequent review of manuscripts identified 124 case reports [7–130] detailing ectopic TT placement, or placement that resulted in patient harm. Our proposed classification algorithm was used to classify the manuscript complications.…”
Section: Resultsmentioning
confidence: 99%
“…Review of abstracts (Fig. 1) led to 155 papers selected for further review, and subsequent review of manuscripts identified 124 case reports [7–130] detailing ectopic TT placement, or placement that resulted in patient harm. Our proposed classification algorithm was used to classify the manuscript complications.…”
Section: Resultsmentioning
confidence: 99%
“…Pseudoaneurysms results from injury to the blood vessel wall [5], accompanying with surgery, trauma, or arterial puncture [6]. Clinically, pseudoaneurysms can be associated with pain or tenderness, as well as aneurysmal bruit on ausculatation or a palpable pulsatile mass on palpation [7].…”
Section: Discussionmentioning
confidence: 99%
“…Epigastric (sub-xiphoid) and chest tube site hernias [71] following cardiac surgery occur in as many as 3-4% of patients following median sternotomy [72]. Another, much less common complications related to the mediastinal tube thoracostomy is superior epigastric artery pseudoaneurysm [73]. Management of these rare conditions is mostly surgical, although minimally symptomatic high-risk surgical patients may be followed with clinical observation.…”
Section: Miscellaneous Gastrointestinal and Abdominal Complications Rmentioning
confidence: 99%